EFFECT OF WHITE OYSTER MUSHROOM (Pleurotus ostreatus) ON CONSUMER ACCEPTANCE OF DRY SMALL SHRIMP (Acetes erythraeus) NUGGET PRODUCTS - Pebri, Arlika; Sukmiwati, Mery; ', Dahlia (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aimed to determine the effect of white oyster mushroom onconsumer acceptance of shrimp nugget products. Dry shrimp used 400g weight byeach addition of different oyster mushroom consists of 4 levels ware, 0% (N0),25% (N1), 50% (N2), and 75% (N3) from the weight of dry small shrimp. Theresults showed that organoleptic test on prefered was N2 (200g). Based onproximate analysis of dry shrimp nugget with 200g (N2) white oyster mushroomaddition were significantly influence on water content (29.72%), ash (36.66%),protein content (19.06%), and crude fiber content (2.38%).Keyword :: White oyster mushroom, dry small shrimp nugget, crude fiber content